(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2022)
This research discussed developing students’ historical comprehension in classroom XI IPA 1 using the ConceptOriented Reading Instruction (CORI) Strategy. This research aims to describe the planning of implementing the CORI strategy in learning history, explain the steps to implementing the CORI strategy, identify students’ historical comprehension through implementing the CORI strategy, and describe the effort to resolve the obstacles in implementing the strategy in learning history. This research is based on the problem that students lack in comprehending historical text that takes effect of students’ historical comprehension. Using the Classroom Action Research with Kemmis and McTaggart, design research consists of several components: plan, act, observe and reflect. The result showed that students’ historical comprehension has increased for each cycle; this research proves that the CORI strategy could be used to develop students’ historical comprehension in learning history.